Microencapsulation: A taste and odour masking approach for garlic (Allium sativum) powder - Sonia Ashfaq Gondal; Nasir Abbas; Amjad Hussain (University of Huddersfield Press, 2018)
The purpose of this study was to prepare a convenient formulation of garlic powder which has enhanced user compliance by suppressing its characteristic odour and masking the taste. Microcapsules of garlic powder were formulated by solvent evaporation method. Results show >80% yield, >70% drug loading efficiency and slow release profile (promising sustained action for more than 2hrs) and a significant reduction in the aromatic smell and taste evaluated through a single blind cross-over study conducted using ten healthy human volunteers.